Eksistensi Tuhan dalam Psikologi: Analisis Psikologi dalam Ayat-Ayat Al-Qur`an - Khoirul Ibad; Artani Hasby; M Ziyad Ulhaq (Universitas Muria Kudus, 2026)
This study appears from the crisis of meaning and spiritual emptiness in modern psychology, which raises fundamental questions about the existence of God in psychological discourse. Rooted in the secular scientific tradition of the West, modern psychology tends to marginalize transcendence and religion in understanding the human being. Major schools—psychoanalysis, behaviorism, humanism, and transpersonal—focus on biological, behavioral, and cognitive aspects while neglecting spirituality and divinity. Employing a qualitative descriptive‑analytical method with comparative analysis between modern psychological theories and Qur’anic texts, this research reveals that secular psychology denies divine existence, emphasizing only material dimensions. In contrast, the Qur’an psychological presents an integral view of the human psyche through divine elements: innate disposition (QS. Ar‑Rum [30]:30), moral inspiration (QS. As‑Syams [91]:7–8), ethical guidance (QS. As-Sad [38]: 71–72,), crisis awareness (QS. Yunus [10]:22), and inner peace through remembrance of Allah (QS. Ar‑Ra’d [13]:28).